Physico-Chemical Properties and Fatty Acid Composition of Gemlik Variety Olives - UYLASER, VILDAN; INCEDAYI, BIGE; ECE TAMER, CANAN; YILMAZ, NESLIHAN; UTKU COPUR, O. (Asian Journal of Chemistry, 2010)
Olive is one of the basic food takes place in the Mediterranean alimentary model. It is an important food on account of its nutritional value besides its economical contribution to national economy. Olive oil is a rich source of essential fatty acids and its fatty acid composition affected from environmental factors and variety. In this study some quality criteria and fatty acid composition of the Gemlik variety olive, one of the most important table olives of Turkey, were examined. Olives grown in 4 different districts of Bursa were used as material. They were analyzed for their number of olive fruit per kg (248 ± 38.05-295 ± 49.32), flesh/stone weight ratio (4.03 ± 0.66-5.64 ± 0.53), pH (5.27 ± 0.15-5.50 ± 0.29), dry matter (47.28 ± 4.92-49.68 ± 3.65 %), protein (2.23 ± 0.29-2.87 ± 0.54 %), reducing sugar (1.98 ± 0.55-2.52 ± 0.32 %), ash (1.58 ± 0.11-1.79 ± 0.52 %), oil (22.74 ± 9.85-31.34 ± 6.67 %) and fatty acid composition. Growing of olives in different districts are actually very near to each other caused the differences of their composition especially flesh/stone weight ratio, protein value and fatty acid composition.